2021
DOI: 10.1186/s12903-021-01721-x
|View full text |Cite
|
Sign up to set email alerts
|

An underestimated pitfall of oral candidiasis in head and neck cancer patients undergoing radiotherapy: an observation study

Abstract: Background Oral candidiasis is a common problem associated with head and neck radiation therapy (RT) consequences being pain, burning sensation, taste change, and systemic infection. There are difficulties in differentiating between oral candidiasis and radiation induced oral mucositis. We conducted a prospective study to explore the incidence of clinical oral candidiasis and evaluate the accuracy of diagnosis among head and neck cancer (HNC) patients receiving RT or concurrent chemoradiotherap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 20 publications
0
11
1
2
Order By: Relevance
“…Lower rates of pseudomembranous candidiasis were found in our study population compared to those reported in other longitudinal studies evaluating the onset of candidiasis during RT treatment of HNC, such as that of Jham et al [30]. A previous study by Chitapanarux et al showed that the clinical and symptom-based analysis of oral candidiasis in irradiated patients with HNC might underestimate the diagnosis and that microbiological analysis may contribute to a higher number of positive diagnoses of this condition [31]. Our study only performed a clinical evaluation of oral candidiasis and not a microbiological analysis, which could explain the differences found since studies showing a high prevalence of this condition in irradiated patients used microbiological analysis to establish the diagnosis.…”
Section: Discussioncontrasting
confidence: 67%
“…Lower rates of pseudomembranous candidiasis were found in our study population compared to those reported in other longitudinal studies evaluating the onset of candidiasis during RT treatment of HNC, such as that of Jham et al [30]. A previous study by Chitapanarux et al showed that the clinical and symptom-based analysis of oral candidiasis in irradiated patients with HNC might underestimate the diagnosis and that microbiological analysis may contribute to a higher number of positive diagnoses of this condition [31]. Our study only performed a clinical evaluation of oral candidiasis and not a microbiological analysis, which could explain the differences found since studies showing a high prevalence of this condition in irradiated patients used microbiological analysis to establish the diagnosis.…”
Section: Discussioncontrasting
confidence: 67%
“…la candidiasis oral debido a factores predisponentes locales como la disminución en la cantidad y calidad de saliva y los daños en la mucosa oral y/o factores predisponentes sistémicos como la inmunosupresión [62][63][64][65] . Es la infección oportunista más frecuente en pacientes que reciben radioterapia por CCC, reportándose en un 25-53% 62,[66][67][68] .…”
Section: Candidiasis Oralunclassified
“…A study of 60 patients with suspected candidiasis reported a 77 % incidence of detection of yeasts, with the most commonly detected species including Candida albicans (48 %), Candida tropicalis (28 %), and Candida parapsilosis (13 %) [83]. Using culture methods, a recent study in 86 patients with HN-SCC undergoing definitive or postoperative radiotherapy where the field included the oral cavity and/or oropharynx also detected a 54 % incidence of oral candidiasis, with the accuracy of clinical diagnosis unaided by microbiological sampling ranging 52-60 % [84]. Although it is tempting to assume that candidiasis is underdiagnosed by about 40 %, it is important to note that Candida is a common commensal of the oral cavity, so detection does not necessarily represent disease.…”
Section: Toxicity Studiesmentioning
confidence: 99%